if you are given the vertex(-3,4) and lets say the information of the parabola is stretched by -2 i know the vertex form is y=-2(x+3)+4 but what is the standard form? thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by william if you are given the vertex(-3,4) and lets say the information of the parabola is stretched by -2 i know the vertex form is y=-2(x+3)+4 but what is the standard form? thanks Expand the turning point form.
Originally Posted by mr fantastic Expand the turning point form. y=-2x-6+4...?
Originally Posted by william y=-2x-6+4...? Doesn't the equation of a parabola contain a squared term? (I had assumed your original post was missing it due to a typo).
Originally Posted by mr fantastic Doesn't the equation of a parabola contain a squared term? (I had assumed your original post was missing it due to a typo). $\displaystyle y=-2(x+3)^2+4$ you are very right $\displaystyle y=-2x^2+9x+4...?$
Originally Posted by william $\displaystyle y=-2(x+3)^2+4$ you are very right $\displaystyle y=-2x^2+9x+4...?$ no. $\displaystyle (x+3)^2 \neq x^2 + 9$
Originally Posted by skeeter no. $\displaystyle (x+3)^2 \neq x^2 + 9$ you're right $\displaystyle (x+3)^2=x^2+6x+9$ so is it $\displaystyle y=-2x^2+6x+9$
Originally Posted by william you're right $\displaystyle (x+3)^2=x^2+6x+9$ so is it $\displaystyle y=-2x^2+6x+9$ No! Please concentrate on getting the algebra correct. Write out all the steps. Don't take short cuts. $\displaystyle y=-2(x+3)^2 + 4 = -2(x^2 + 6x + 9) + 4 = -2x^2 - 12x - 18 + 4 = -2x^2 - 12x - 14$.
Originally Posted by mr fantastic No, Please concentrate on getting the algebra correct. Write out all the steps. Don't take short cuts. $\displaystyle y=-2(x+3)^2 + 4 = -2(x^2 + 6x + 9) + 4 = -2x^2 - 12x - 18 + 4 = -2x^2 - 12x - 14$. thanks
View Tag Cloud